Mindful aging: an insightful examination of cognitive impairment in the elderly population of Chengalpattu, Tamil Nadu, using Mini-Cog scale - M., Vinoth Kumar; D., Thirunaaukarasu; M., Geetha; D., Catherine Rexy (International Journal Of Community Medicine And Public Health, 2024)
Background: By 2050, United Nations projects that one in five Indians would be 60 years of age or older. This demographic transition is likely to be accompanied by substantial rise in prevalence of cognitive problems, which will have an impact on quality of life among elderly people. Effective screening at primary level would help in identification of burden of diseases and better planning at secondary and tertiary level. Methods: A community-based cross-sectional study over a period of three months was conducted at Pulipakkam in Chengalpattu district. The estimated sample size was 215, and simple random sampling method was used. Elderly people aged 60 years and above who consented to participate were included in the study. After obtaining informed consent, they were screened using the Mini-Cog tool which combines a short memory test with a simple clock- drawing test followed by a recall component. Results: The 215 participants in total were screened. The mean age of participants was 66.02±3.83 years. The prevalence of cognitive impairment (CI) based on Mini-Cog scale was 44.2%. Females (44.8%) had marginally higher prevalence than males (43.8%). CI was more prevalent among people over 65 years (57.6%). The likelihood of experiencing CI was higher among those who lived without their spouse (59.4%), were unemployed (53.7%), and who were smokers / alcoholics (63.7%). Conclusions: Considering the high burden of CI, there is need for long term prospective research for a comprehensive profile of mental disorders at community level. Early assessment and detection of CI could help in improving quality of life of elderly. Implementing initiatives aimed at increasing awareness, reducing stigma, and conducting widespread screening using reliable tools.